The surgical treatment of acromegaly - Buchfelder, Michael; Schlaffer, Sven-Martin (Pituitary, 2017)
PURPOSE: Surgical extraction of as much tumour mass as possible is considered the first step of treatment in acromegaly in many centers. In this article the potential benefits, disadvantages and limitations of operative acromegaly treatment are reviewed. METHODS: Pertinent literature was selected to provide a review covering current indications, techniques and results of operations for acromegaly. RESULTS: The rapid reduction of tumour volume is an asset of surgery. To date, in almost all patients, minimally invasive, transsphenoidal microscopic or endoscopic approaches are employed. Whether a curative approach is feasible or a debulking procedure is planned, can be anticipated on the basis of preoperative magnetic resonance imaging. The radicality of adenoma resection essentially depends on localization, size and invasive character of the tumour. The normalization rates of growth hormone and IGF-1 secretion, respectively, depend on tumour-related factors such as size, extension, the presence or absence of invasion and the magnitude of IGF-1 and growth hormone oversecretion. However, also surgeon-related factors such as experience and patient load of the centers have been shown to strongly affect surgical results and the rate of complications. As compared to most medical treatments, surgery is relatively cheap since the costs occur only once and not repeatedly. There are several new technical gadgets which aid in the surgical procedure: navigation and variants of intraoperative imaging. CONCLUSIONS: For the mentioned reasons, current algorithms of acromegaly management suggest an initial operation, unless the patients are unfit for surgery, refuse an operation or only an unsatisfactory resection is anticipated. A few suggestions are made when a re-operation could be considered.
EVALuna2:102202